2006
DOI: 10.1002/pros.20328
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic and expression profiles associated with transformation to androgen-resistant prostate cancer

Abstract: Our findings may serve as a basis for molecular dissection of the mechanisms involved in development of androgen resistant prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Third, and again highlighting their biological importance, all the genes in our novel disease signature are located at regions of deletions or chromosomal break points in prostate cancer. [48][49][50] It is therefore possible that genomic rearrangements may be the primary reason for their altered expression in prostate cancer. This idea is in accordance with a recent large-scale genomic study of prostate tumors, which found that copy-number alterations are more robust stratifiers of disease grade than mRNA or miRNA expression profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Third, and again highlighting their biological importance, all the genes in our novel disease signature are located at regions of deletions or chromosomal break points in prostate cancer. [48][49][50] It is therefore possible that genomic rearrangements may be the primary reason for their altered expression in prostate cancer. This idea is in accordance with a recent large-scale genomic study of prostate tumors, which found that copy-number alterations are more robust stratifiers of disease grade than mRNA or miRNA expression profiles.…”
Section: Discussionmentioning
confidence: 99%
“…A putative epigenetic gene signature including genes involved in DNA methylation (DNMT3A and MBD4), histone methyltransferases (MLL2, MLL3, and NSD1), and the histone acetyltransferase (SRCAP) was identified. Whereas DNMT3A and MBD4 have previously been found to be altered in prostate cancer (39,57), this is not the case for MLL2, MLL3, SRCAP, and NSD1 (reviewed in ref. 26).…”
Section: Discussionmentioning
confidence: 99%
“…To date, no specific role for DNMT3A has been shown for genitourinary tract developmental processes, although a myriad of developmental abnormalities results from deleting Dnmt3a in mouse models and conditional Dnmt3a mutant males show impaired spermatogenesis (46). Studies in prostate cancer have shown increased Dnmt3a expression in tumors developing in the TRAMP model (47), and increased DNMT3A expression has been associated with progression to androgen-independent growth in vitro (47,48). SLC43A1 encodes a protein that functions in the sodium-independent transport of neutral amino acids.…”
Section: Discussionmentioning
confidence: 99%